2020
DOI: 10.1186/s12936-020-03384-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Plasmodium falciparum in Grande Comore Island

Abstract: Background: Despite several control interventions resulting in a considerable decrease in malaria prevalence in the Union of the Comoros, the disease remains a public health problem with high transmission in Grande Comore compared to neighbouring islands. In this country, only a few studies investigating the genetic diversity of Plasmodium falciparum have been performed so far. For this reason, this study aims to examine the genetic diversity of P. falciparum by studying samples collected in Grande Comore in 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…Interestingly, the RO33 allelic family was not found in Central Kalimantan Province. This result is different with that found in Pahang, Malaysia, where RO33 allelic family was predominant as monomorphic ( 38 ), in contrast with that found in Grande Comoro Island where RO33 allelic family were poorly represented (2.4–4.0%) ( 39 ), while in Myanmar-China border was higher (12.56%) ( 17 ). In Gabon, when the DNA was isolated from RDTs showed that K1 (93.9%) was found higher than MAD20 (73.3%) ( 40 ).…”
Section: Discussioncontrasting
confidence: 89%
“…Interestingly, the RO33 allelic family was not found in Central Kalimantan Province. This result is different with that found in Pahang, Malaysia, where RO33 allelic family was predominant as monomorphic ( 38 ), in contrast with that found in Grande Comoro Island where RO33 allelic family were poorly represented (2.4–4.0%) ( 39 ), while in Myanmar-China border was higher (12.56%) ( 17 ). In Gabon, when the DNA was isolated from RDTs showed that K1 (93.9%) was found higher than MAD20 (73.3%) ( 40 ).…”
Section: Discussioncontrasting
confidence: 89%
“…Furthermore, of 192 positive samples for P. falciparum , less than half showed an amplicon for msp-1 (n = 97) or msp-2 (n = 95). In previous studies, relatively higher numbers of amplicons were observed for msp-1 or msp-2 ( Somé et al, 2018 ; Mohammed et al, 2019 ; Eltayeb et al, 2020 ; Papa Mze et al, 2020 ). The nonspecific binding during P. falciparum identification by PCR may justify the smaller number of amplicons for msp-1 and msp-2 in the current study.…”
Section: Discussionmentioning
confidence: 83%